Generating and Analysing Data for Applied Research on Emerging Technologies: A Grounded Action Learning Approach - Pak Yoong; David Pauleen (Information Research: An International Electronic Journal)
One of the difficulties of conducting applied qualitative research on the applications of emerging technologies is finding available sources of relevant data for analysis. Because the adoption of emerging technologies is, by definition, new in many organizations, there is often a lack of experienced practitioners who have relevant background and are willing to provide useful information for the study. Therefore, it is necessary to design research approaches that can generate accessible and relevant data. This paper describes two case studies in which the researchers used a grounded action learning approach to study the nature of e-facilitation for face-to-face and for distributed electronic meetings. The grounded action learning approach combines two research methodologies, grounded theory and action learning, to produce a rigorous and flexible method for studying e-facilitation. The implications of this grounded action learning approach for practice and research will be discussed.